Application of laser scanning cytometry in vascular smooth muscle remodeling. Issue 11 (November 2018) - Johar, Dina; Magdeldin, Sameh
Abstract Pulmonary artery hyperplasia is the result of proliferation of the pulmonary arterial smooth muscles (PASM). Hypoxia-induced PASM proliferation in the fetus and the newborn is the primary cause of persistent pulmonary hypertension of the newborn (PPHN). This study was performed to characterize the utility of the Laser Scanning Cytometry (LSC) method in elucidating arterial cytoskeletal remodeling in an in vitro model of PPHN. The aim was to demonstrate the following: (a) LSC is a valid method for the analysis of nuclear and cytosolic fluorescence and (b) the cumulative effects of mechanical stretch together with hypoxia promote reactive oxygen species (ROS) formation. The molecular events in response to hypoxia and the mechanical overload of the pulmonary circuit were demonstrated in vitro by subjecting hypoxic cultured primary PASM or human airway smooth muscles (hASM) to repetitive stretch-relaxation cycles at rates comparable to dynamic stretch in vivo. The altered cytoskeleton in the form of filamentous to globular actin (F:G actin) ratio was imaged and quantified at the cellular level by LSC as an endpoint. LSC can remove the nuclear G-actin fluorescence from the total G-actin fluorescence. Pulsatile stretch was found to significantly increase the total endogenous ROS and superoxide anion release in normoxic and hypoxic conditions in primary PASM fibers. The effect of stretch was predominant in increasing superoxide anion release, only under hypoxic conditions. These findings, obtained by LSC in vitro are amenable to validation in any in vivo model of interest. The in vitro model is clinically relevant to human pulmonary vascular remodeling.